Pengenalan Marketplace Hingga Robot Line Follower: Inovasi KKN Tematik di Dusun Gunungsari Desa Mlarak Kabupaten Ponorogo - Arief Rahman Yusuf; Fikrun Najib Muzakki (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2024)
The Thematic Community Service Programme in Gunungsari Subvillage, Mlarak Village, Ponorogo Regency strives to introduce digital technology and robotics to locals. This initiative concentrates on two key areas: introducing marketplaces to local UMKM and educating youth about line follower robots. The program aims to reduce the digital gap, enhance local economic competitiveness, and spark technological interest among young people. The program's execution involves two primary phases. The first phase focuses on familiarizing and training UMKM in marketplace usage, covering account setup, online store operations, and digital marketing tactics. The second phase comprises workshops and demonstrations of line follower robots at local schools, engaging students in basic robot programming and operation. The approach includes interactive sessions, hands-on training, and personalized guidance for participants. The initiative successfully enhanced the marketplace skills of 10 UMKM, with 60% of them beginning to market their products online actively. Concurrently, the line follower robot introduction attracted 60 students, resulting in a 75% increase in their interest in robotics technology, as indicated by post-event surveys. Furthermore, the program fostered collaboration among students, community members, and local government in efforts to advance technology and boost the local economy.